Relation of dental caries with the risk of barodontalgia among professional divers: Hubungan karies gigi dengan resiko baradontalgia pada penyelam profesional - Ningrum, Reviana Anggreini; Herdiansyah, M. Aidil Sultan; Azzahra, Fatimah; Dharma, Muhammad Akira Takashi (Makassar Dental Journal, 2025)
Barodontalgia is pain in the teeth triggered by changes in air pressure during diving, and is a common complaint among profes-sional divers. One of the main risk factors for barodontalgia is poor dental health, particularly active caries or imperfect restorati-ons. This article systematically reviews the latest scientific evidence on the relationship between dental caries and the risk of ba-rodontalgia in professional divers. The article search was conducted through the PubMed, Scopus, and ScienceDirect databases. The prevalence of barodontalgia in divers is 10.8-56.1%, generally caused by caries and leaky restorations. It is concluded that comprehensive dental screening and treatment should be part of the medical protocol before diving to minimise the risk of dental pain and improve diver safety.